Role of Nanoparticles in Enzymatic Hydrolysis of Lignocellulose in Ethanol - Rai, Mahendra; Ingle, Avinash P.; Gaikwad, Swapnil; Dussan, Kelly J. [UNESP]; Silva, Silvio Silverio da; Rai, M.; DaSilva, S. S. (Springer, 2017)
The depletion in the limited sources of fossil fuels has generated the problem of energy crisis all over the world. This hunt forces scientific community towards the search for cost-effective, environment-friendly, renewable alternative sources which can replace fossil fuels and fulfill the increasing demands of energy. In this context, the use of lignocellulosic material (plant residues) composed of cellulose, hemicellulose, and lignin becomes the first choice. In the process of ethanol production, first lignocellulosic material is broken down and hydrolyzed into simple sugars like cellulose, and then these sugars are fermented into biofuels such as ethanol in the presence of enzymes like cellulases. The use of cellulases makes the process expensive, and therefore, immobilization of these enzymes on solid supports like nanoparticles can help to recover the enzyme, which ultimately decreases the cost of process. Therefore, the use of nanotechnology and nanomaterials could be one possible avenue to improve biofuel production efficiency and reduction in the processing cost. This chapter discusses important existing pretreatment approaches involved in the pretreatment of plant biomass use for biofuel production. The emphasis is given on the role of nanotechnological solutions for the development of novel, efficient, and inexpensive strategies for the production of biofuels.
Keywords: Biofuel; Ethanol; Fossil fuels; Nanotechnology; Pretreatments